Komposisi Botani dan Kapasitas Tampung Padang Pengembalaan Anduna Kecamatan Laeya Kabupaten Konawe Selatan - Zulfiqhi Haris; Widhi Kurniawan; La Ode Nafiu (Jurnal Ilmiah Peternakan Halu Oleo, 2023)
This study aimed to analyze the botanical composition and carriying capacity of the Anduna grazing land in laeya subdistrict, South Konawe Regency. This research was carried out from July to August 2022, which took place in the Anduna grazing area, Laeya subdistrict, South Konawe Regency. Lembo District, North Konawe Regency. The materials used in this study were forage grass, legumes, and weeds with a total of 120 samples in 6 different paddocks, each paddock has an area of 10 hectares. The variables observed in this study are botanical composition including grasses, legumes and weeds dan the carrying capacity. The results of this study indicate that the composition of fresh forage was dominated by grass 69,00%, legumes 5,12% and weeds 25,88%.